Blade Runner 2019. [Vol. 1], Los Angeles - Green, Michael (Screenwriter); Johnson, Mike (Comic book author) (Titan Comics, 2019)
"LAPD's best Blade Runner and detective, Aahna "Ash" Ashina, has been assigned to investigate the mysterious disappearance of Isobel and Cleo Selwyn, the wife and daughter of business tycoon, Alexander Selwyn--a close personal friend of Eldon Tyrell. Ash's search will take her on a journey deep into the crime-ridden underbelly of Los Angeles--a slowly decaying megacity--as she uncovers a terrible secret and a desperate conspiracy that forces her to confront her own hatred for Replicants--the synthetic humans--that she hunts and kills with such vengeance."--Page 4 of cover